Teachers’ Perceptions of Using Visual Media to Teach English Vocabulary to Students with Autism Spectrum Disorder - Khairun Nisa; Emeliya Sukma Dara Damanik (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study explored teachers’ perceptions of using visual media in teaching English vocabulary to students with Autism Spectrum Disorder (ASD) and the challenges encountered during its implementation. Employing a descriptive qualitative design, the study involved one English teacher at an inclusive elementary school in Indonesia. Data were collected through semi-structured interviews and documentation and analyzed using thematic analysis. The findings revealed that visual media helped students maintain attention, understand vocabulary more easily, and retain vocabulary more effectively. Flashcards were identified as the primary visual medium used in instruction, supported by visual schedules and picture-based worksheets. Students also showed positive responses through increased participation and engagement. However, challenges such as loss of focus, boredom, and tantrums occasionally affected the learning process. The study concludes that visual media are effective instructional supports for teaching English vocabulary to students with ASD, while their successful implementation requires teachers’ flexibility in addressing students’ diverse learning needs.